2020
DOI: 10.3390/microorganisms8091316
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Bacteriophage Cocktail to Complement Commercial Sanitizer Use on Produce against Escherichia coli O157:H7

Abstract: The increasing concern for food safety has created a need to evaluate novel techniques to eliminate or control pathogens, resulting in safe food. In this study, four bacteriophages of bovine origin, specific to E. coli O157:H7, were successfully isolated and characterized. A microplate reader assay demonstrated the efficacy of the bacteriophage (phage) cocktail against E. coli O157:H7 resulting in a significant reduction (p < 0.01) in the target pathogen population. The phage cocktail demonstrated significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Because phages are ubiquitous, the isolation of new phages specific to the pathogen that exhibits a difference in the attachment mechanism can be used to update phage cocktails and make them effective against the development of phage-resistant mutant strains. Although the use of bacteriophages requires that investigators exercise caution to ensure their specificity against the target pathogen, the bacteriophage cocktails used in this study have been previously investigated for their specificity and also have demonstrated infectivity only for E. coli O157:H7 strains [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because phages are ubiquitous, the isolation of new phages specific to the pathogen that exhibits a difference in the attachment mechanism can be used to update phage cocktails and make them effective against the development of phage-resistant mutant strains. Although the use of bacteriophages requires that investigators exercise caution to ensure their specificity against the target pathogen, the bacteriophage cocktails used in this study have been previously investigated for their specificity and also have demonstrated infectivity only for E. coli O157:H7 strains [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing the phage concentration might help achieve a more significant reduction of the pathogen during produce wash. Environmental conditions can also play a significant role in a phage’s viability; thus, studying the effect of these conditions will help to ensure the continuous performance of the phage against the pathogen. Phages employed for this study have also been shown to be resistant to 100-ppm chlorine and 100-ppm SaniDate 5.0 for up to 3 h [ 19 ]. Thus, developing a multilevel sanitation system that employs both a sanitizer and bacteriophage combination might be one of the solutions to reduce pathogen contamination on fresh produce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of STEC with produce presents a serious problem because these products are minimally processed. Moreover, STEC strains have been shown to be adapted to survive for prolonged periods on plants and are often resistant to washing and chemical sanitizers [ 5 , 6 , 7 , 8 ]. As a result, contamination of fresh produce is emerging as a major food safety challenge, suggesting that current strategies to control microbial population during the production of fresh produce do not guarantee the elimination of STEC [ 2 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%